(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the essence of inclusive education, its basic principles and practical methods of application. Inclusive education is considered as an educational system that allows children with different needs to study and develop together. The article discusses the impact of inclusion on society, the role of teachers and parents, as well as the obligations of educational institutions in this regard. According to the results of the study, the inclusive education system serves to improve the quality of education, strengthen social integration and strengthen the principles of justice in society.